Relative Risk for a Class of Patients Based on Progressive Censored Data Exposed to Radiations Using Cox’s Proportional Hazard with a Set of Covariates (Journal of Atomic, Molecular, Condensed Matter and Nano Physics, 2022)
An attempt has been made to estimate Relative Risks (RR) of a category of patients assumed to be progressive censored and exposed to multiple hazards including nuclear radiations and suffering from chronic non-communicable disease by fitting Cox’s proportional hazard regression model. Covariates are different age groups of patients, nature of stages of patients and treatment given to patients. The time dependent Weibull hazard rates have been estimated by using Maximum likelihood method. Any one of the three covariates considered here is taken as poorer immunity of a section of population because of exposure to high energy radiation of different kinds. The Relative Risk and Longevity estimates can further be used to construct life tables for such class of population, considering the censoring aspect of the data.
Keywords: Covariates; Hazard rate; Progressive censoring; Relative risk